ФІНАНСОВЕ ЗАБЕЗПЕЧЕННЯ СОЦІАЛЬНО-ЕКОНОМІЧНОГО РОЗВИТКУ ТЕРИТОРІАЛЬНИХ ГРОМАД - Далевська, Тетяна Анатоліївна (Науковий журнал «Світ фінансів», 2017)
Далєвська Т. А. Фінансове забезпечення соціально-економічного розвитку територіальних громад. Поглиблено поняття фінансового забезпечення соціально-економічного розвитку, обґрунтовано доцільність посилення ефективності функціонування механізму фінансового забезпечення розвитку територіальних громад. Запропоновано трактування понять “фінансова самостійність” та “фінансова самодостатність” бюджетів територіальних громад, визначено методологічні засади оцінки соціально-економічного розвитку територій на основі розрахунку інтегрального коефіцієнта розвитку. Проаналізовано питому вагу капітальних видатків у структурі зведених бюджетів місцевого самоврядування Вінницької області та визначено шляхи підвищення ефективності механізму фінансового забезпечення місцевого самоврядування. Далевская Т. А. Финансовое обеспечение социально-экономического развития территориальных обществ. Углублено понятие финансового обеспечения социально-экономического развития, исследованы и обоснованы целесообразность усиления эффективности функционирования механизма финансового обеспечения развития территориальных общин. Предложены трактовки понятий “финансовая самостоятельность” и “финансовая самодостаточность” бюджетов территориальных общин, определены методологические основы оценки социально-экономического развития территорий на основе расчета интегрального коэффициента развития. Проанализирован удельный вес капитальных расходов в структуре сводных бюджетов местного самоуправления Винницкой области и определены направления повышения эффективности механизма финансового обеспечения местного самоуправления. Dalevska T. Financial support of territorial communities’ socio-economic development. Introduction. In conditions of economic transformations it is determined the need to strengthen the impact of the financial support of local governments on social and economic development and welfare of local communities. Purpose. Definition of financial security communities as an effective tool of territories’ economic development and forming the system of indicators measure communities’ social and economic development in order to strengthen the manageability of local finances management mechanism. Results. The basic level budgets play an important role in financial support of socioeconomic development of administrative-territorial units, as well as accumulate the financial resources necessary for satisfaction communities’ social needs. The level of administrative units’ development depends on the effectiveness of the financial security of local government, because financial opportunities are the source of economic development, qualitative strengthening of social security, financing needs, an instrument of economic restructuring and beautification. It is advisable to distinguish the concept of financial self-sufficiency of communities budgets and financial autonomy Financial self-sufficiency is a conditions that can be expressed as an equilibrium of local budgets’ expendable and financial capacity. Financial autonomy is characterized by the increasing dominance of the territorial communities’ financial capacity. The economically developed communities effectively use financial strength and have a high level of financial independence of local budgets. In the context of functional classification of consolidated expenditures of local budgets the largest share in 2005-2015 occupied the expenditures on education, which accounted for 29.4% of expenditures local government budgets.95% of the budgets of local communities of cities and villages of Vinnitsa region carry out development budget expenditures, their share in the average for 2004-2014. Is in the range of 10-20% of the total expenditures of local government. It is necessary to increase the volume of capital expenditures of Vinnitsa region local government. budgets. Conclusion. Results of the analysis show that there is a need to strengthen the financial autonomy of local communities, improving the feasibility of the division of powers between local authorities and local authorities. To improve the effectiveness of the financial support of local government economic development, there is need for increasing financial capacity, improving the competitiveness of the community, such as capacity to ensure the production of competitive goods and services in terms of efficient use of factors of production and create conditions for economic growth.